Severe intraprocedural complications after transcatheter aortic valve implantation: calling for a heart team approach† - Moritz Seiffert; Lenard Conradi; Stephan Baldus; Johannes Schirmer; Stefan Blankenberg; Hermann Reichenspurner; Patrick Diemert; Hendrik Treede (2013)
Transcatheter aortic valve implantation (TAVI) has emerged rapidly. Despite unanimous recommendations and potentially fatal intraoperative complications, the heart-team approach is not comprehensively adopted by all centres. We sought to characterize severe intraprocedural complications during TAVI requiring immediate surgical or interventional bailout manoeuvres and evaluate outcomes. TAVI was performed in 458 consecutive patients using a balloon-expandable or self-expanding valve through transfemoral and transapical approaches. Severe intraprocedural complications requiring intraoperative bailout manoeuvres were analysed according to the Valve Academic Research Consortium (VARC) criteria. Thirty-five of 458 patients (7.6%) experienced 40 major intraprocedural complications during TAVI, 13 (2.8%) requiring emergent conversion to surgery. Complications included valve embolization/migration (17%), severe aortic regurgitation (12%) and root rupture (5%), requiring immediate implantation of a second valve or conversion to surgical valve replacement. Sternotomy and surgical haemostasis were performed in 5 patients (13%) with left ventricular wire perforation and subsequent cardiac tamponade. Coronary obstruction (15%) required emergent percutaneous coronary intervention in 6 patients. At 30 days, all-cause mortality was 31.4% in patients with intraprocedural complications and 38.5% in patients requiring surgical conversion. However, mid-term survival after 30 days and exercise tolerance in surviving patients were comparable with patients undergoing uncomplicated TAVI. An interdisciplinary approach to TAVI facilitated bailout procedures accomplishing acceptable outcomes, despite severe intraprocedural complications. These bailout manoeuvres in potentially fatal complications were only accomplished through an interdisciplinary heart-team effort, creating a surgical and interventional safety net, which should be established in all centres performing TAVI procedures.